1968
DOI: 10.1364/ao.7.001159
|View full text |Cite
|
Sign up to set email alerts
|

Far Infrared Reflection Spectra of AgCl, AgBr, and AgI at Low Temperatures

Abstract: The reflection spectra of AgCl, AgBr, and AgI are measured at liquid hydrogen, liquid nitrogen, and room temperatures. For AgCl, they show distinctly two components. For AgBr and AgI, the structure, though complex, is not resolved. Nevertheless, in all cases, except for AgI, at low temperature, the Lorentz analysis needs two oscillators. The stronger one v(1) corresponds to the TO transition at point Gamma, the second one v(2), about an order of magnitude smaller, corresponds to a TA + TO addition band for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
2

Year Published

1972
1972
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 11 publications
0
6
1
2
Order By: Relevance
“…I n this model the mode behaviour of the mixed crystal can be predicted from macroscopic parameters of the pure end members. Since the static and high-frequency dielectric constants from our KK analysis were not of sufficient, accuracy, we took for both AgBr and AgCl from [6]. Using then our values for the L O and TO long-wavelength frequencies the corresponding E~ was computed by means of the LydanneSachs-Teller relation.…”
Section: Resultsmentioning
confidence: 99%
“…I n this model the mode behaviour of the mixed crystal can be predicted from macroscopic parameters of the pure end members. Since the static and high-frequency dielectric constants from our KK analysis were not of sufficient, accuracy, we took for both AgBr and AgCl from [6]. Using then our values for the L O and TO long-wavelength frequencies the corresponding E~ was computed by means of the LydanneSachs-Teller relation.…”
Section: Resultsmentioning
confidence: 99%
“…In the far-IR region, Hadni et al [6] reported the optical constants determined by a K-K analysis at room temperature (shown in Table V), 80 K, and 25 K. The experimental procedure was the same as in the case of AgC1, but the samples were not single crystals; they were pellets. Two Lorentz oscillators were also needed for AgBr; the stronger one corresponds to the TO mode and the weaker one to the TA + TO mode (see Table II).…”
Section: Agbr (Cubic)mentioning
confidence: 99%
“…In the far-IR, Hadni et al [6] reported the effective optical constants shown in Table VI obtained by K-K analysis. The experiment was the same one as in the case of AgC1, except that the samples were not single crystals, but pellets.…”
Section: /3-agl (Hexagonal) Stable For T < T C = 147 ~ C Iiimentioning
confidence: 99%
See 1 more Smart Citation
“…the J T splitting AE increases with increasing temperature. I n Table 3 the measured shifts AE(300 " K ) / A E ( 2 0 OK) are compared with the shifts calculated with (4.1) using the values A w~o = wT0(20 O K ) -wTo(3o0 OK) given byHadiii et al [19]. I n consideration of the uncertainty of the assumption AoE/o, = = AcuTO/cuTO i t seems justified to conclude that the weak temperature dependence of AE is caused by that of me.…”
Section: Oscillator Strengthsmentioning
confidence: 99%